Glacio-environmental aspects recorded in two shallow ice cores drilled in 1980 at accumulation area of Khumbu Glacier of Mt. Everest in Nepal Himalayas. Issue 1 (1st January 2020) - Takeuchi, Nozomu; Hori, Yoichiro; Furukawa, Noboru; Yoshida, Minoru; Fujii, Yoshiyuki
ABSTRACT: The physical and geochemical characteristics of shallow ice cores drilled in the accumulation area (Western Cwm) of Khumbu Glacier in the Nepal Himalayas in 1980 were analyzed. The two ice cores from different elevations (cores 1 and 2 from 6, 100 and 6, 400 m a.s.l., respectively) showed distinct stratigraphy: Core 1 consisted of stratified firn layers with a few ice and dust layers, whereas core 2 consisted of unstratified refrozen ice with abundant debris. The mean oxygen-stable isotope was significantly lower in core 2 than in core 1, and the composition of major soluble ions also differed between the ice cores. The mineralogical characteristics of debris in core 2 were in accordance with the geology of the south face of Mt. Everest, indicating that it was supplied from above 7, 000 m a.s.l. by avalanches. The distinct stratigraphy and geochemistry suggest that the snow accumulation process differed between the two drilling sites; snow was supplied by precipitation in core 1, whereas in core 2 it was supplied by avalanche with rock debris from the higher site of the south face of Mt. Everest. The two distinct snow accumulation processes are likely to characterize the mass balance and formation of debris covers of the lower ablation area of Khumbu Glacier.